PENERAPAN ISTISHÂB DALAM KASUS AHLI WARIS YANG HILANG (MAFQŪD) ATAU TIDAK DI KETAHUI KEBERADAANNYA - Faizah, Isniyatin; Izza, M. Syafi’ Nuril; Najib, M. (Al Hakam : The Indonesian Journal of Islamic Family Law and Gender Issues, 2025)
Islamic inheritance law is a critical aspect that Muslims are required to study as part of fardu kifayah, in accordance with the teachings of the Prophet Muhammad. A key challenge in this domain is the case of a missing heir, or mafqūd, whose unknown whereabouts often trigger disputes over the ownership of inherited assets. This study aims to investigate the role of Istishāb, an Islamic legal method that maintains the existing legal status until evidence emerges to change it, in addressing cases of missing heirs. Employing a qualitative approach through document analysis, this research explores the definition of Istishāb as understood by ushul fiqh scholars, its relevance to inheritance law, and its application in determining the status of a mafqūd. The findings reveal that Istishāb plays a significant role in ensuring justice and legal certainty by presuming the missing heir is alive until proof of death is established, thereby protecting the rights of other heirs. The study also elaborates on the perspectives of fiqh scholars, the supporting shar’i evidence, and the procedures for determining the status of a mafqūd, including the freezing of the inheritance share until legal certainty is achieved. Thus, Istishāb functions not only as a legal tool but also as a mechanism to ensure social justice in the distribution of inheritance.